Effect of weaning on performance of dairy buffaloes in tropical conditions - A review - P K Bharti; PRACHURYA BISWAL; REENA KAMAL; BHANITA DEVI; TRIVENI DUTT (Indian Journal of Animal Sciences, 2022)
Weaning is one of the important management practices, which is mostly followed at organized dairy farms in India and abroad. Generally breeding programme at buffalo farms focusses on milk production, however weaning can additionally boost the total milk production of the dairy farm, apart from increasing the reproductive potential of adults and promoting scientific rearing of young calves. There is little information on early weaning of buffalo calves and its effect on production and reproduction performances of dams during post-partum in Indian buffaloes. However, early weaning may be associated with the restriction of colostrum feeding and essential nutrients for dairy buffalo calves. Breaking the maternal bond is stressful to the calf and lactating buffaloes, which can be evaluated by biochemical indicators of stress in bovine models. Although, weaning at birth is well established in dairy cattle, in case of buffaloes, it may yield significant outcomes in terms of estimating actual milk production and increasing precious buffalo milk in the market for human consumption. On the other hand, weaning practice in dairy buffaloes has been limitedly investigated and not reviewed properly under variable conditions. Keeping in view the impact of weaning, the present paper has been aimed to review the effect of weaning on performance of dairy buffaloes under tropical conditions. The weaning practices in dairy buffaloes can reduce the feeding cost of calves and increase the reproductive potential of the dairy animals through early resumption of post-partum ovarian cyclicity. However, more trials need to be conducted in dairy buffaloes for understanding the relationship between the behaviour of weaned animals and age of weaning towards better adaptability and optimum production at dairy farms.